HOPE FROM THE ASHES: A TRAUMA-HERMENEUTIC READING OF LAMENTATIONS 3 IN THE CONTEXT OF COLLECTIVE CRISIS - Alvin Budiman Kristian (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2026)
Issues ranging from post-pandemic trauma to escalating global violence have triggered a spiritual silence and a theological crisis regarding the existence of God. This article aims to formulate a grounded theology of hope through a trauma-hermeneutic reading of Lamentations 3. Employing a qualitative-interpretative method that analyzes poetic structure and transitions, the research reveals that the triple alphabetic acrostic structure of Lamentations 3 is not merely a literary device but an instrument of cognitive containment that organizes the chaos of traumatic experience. The study’s novelty lies in positioning verses 21–22 as a *locus theologicus*, where wounds are understood not as the absence of God, but as a revelatory space for divine *hesed* (steadfast love) at work "between" destruction and restoration. Ultimately, Lamentations 3 offers a model of hope that is not naive—a hope born from the depths of the ashes of suffering. This study contributes significantly to the church's pastoral praxis in accompanying grieving communities by validating narratives of woundedness as an integral part of the journey of faith.